099 Acute changes in coronary haemodynamic in patients undergoing transcatheter aortic valve implantation. (22nd September 2015) - Davies, J E; Sen, S; Hadjiloizou, N; Francis, D P; Foale, R A; Mayet, J; Parker, K H; Hughes, A D; Chukwuemeka, A; Mikhail, G; Malik, I S
Abstract : Introduction: Aortic stenosis (AS) and left ventricular hypertrophy (LVH) detrimentally alter coronary haemodynamics and increase mortality. However, it has never been possible to discriminate between the effects of severe left ventricular pressure loading and chronic changes of LVH. We assessed this invasively in subjects before and immediately after transcatheter aortic valve implantation (TAVI). Methods: In 26 subjects (35–91years) coronary artery pressure and flow velocity were measured using intra-arterial wires. 3 cohorts with unobstructed arteries were assessed: (1) No LVH (n=10), (2) LVH (n=11), and (3) AS and LVH undergoing TAVI (n=6). To quantify the effects that pressure loading and LVH have on coronary haemodynamics wave separation was performed using wave intensity analysis, and physiological reserve assessed by pacing Results: In subjects without AS, LVH was associated with a reduction in myocardial suction wave (6.1±4 v 3.1±2×10 −5 Wm −2  s −1, p=0.03). In TAVI subjects this wave was lower in comparison to LVH group (2.2±1×10 −5 Wm −2  s −1, p<0.001), and decreased further with pacing (90 bpm;1.2±0.6 and 120bpm;1.2±0.7 x10 −5 Wm −2 s −1 respectively p=0.03 for both). Post-TAVI the suction wave fell markedly (2.2±1 v 0.8±0.5×10–5 Wm −2  s −1, p=0.01) below that seen in subjects with unobstructed arteries and LVH without AS (3.1±2×10 −5 Wm −2  s −1, p<0.01). Conclusions: Aortic stenosis and LVH are independently detrimental to coronary haemodynamics. Despite relief of aortic obstruction coronary haemodynamics remains impaired after TAVI probably due to the deleterious effects of severe LVH. With regression of LVH after successful treatment, normalisation may occur.